HIV-1 is Transported into the Central Nervous System by Trafficking Infected Cells - Laura Kincer; Gretja Schnell; Ronald Swanstrom; Melissa Miller; Serena Spudich; Joseph Eron; Richard Price; Sarah Joseph (Pathogens and Immunity, 2023)
Background: In this work, we carried out a cross-sectional study examining HIV-1 and HCV free virus concentrations in blood and cerebrospinal fluid (CSF) to determine whether HIV-1 enters the central nervous system (CNS) passively as virus particles or in the context of migrating infected cells. If virions migrate freely across the blood-cerebrospinal fluid barrier (BCSFB) or the blood-brain barrier (BBB) then HCV and HIV-1 would be detectable in the CSF at proportions similar to that in the blood. Alternatively, virus entry as an infected cell would favor selective entry of HIV-1.